A relação entre caipiras e o processo de urbanização na música sertaneja entre as décadas de 1920 e 1980 - Jóyce Oliveira Leitão (Confins)
Although the Caipira culture may seem strange to capitalist society, it is a result of a historical exclusion of land propriety that reached traditional communities from the period of colonial Brazil until the last decades of the 20th century. This exclusion led to the expulsion of caipiras from rural areas and compelled them to the live and work in the cities. The intensification of the expulsion of these workers from rural areas and the quick urbanization coincided with the emergence of sertaneja music and widespread consumption of products linked to this music, like radio programs and records. We seek to identify the relationship between sertaneja music produced from 1920 to 1980 and the migration processes. This relationship is analyzed in order to understand how sertaneja music corresponds to a caipira position about the urbanization process.